Development of Braille Number Card As Learning Media on Integer Materials for Blind Students - Igirisa, Shendy S; Fuad, Yusuf; Ismail, Sumarno (Universitas Malikussaleh, 2019)
Losing vision for blind students makes them difficult to access education. Thus, blind students need special tools like interesting and applicable learning media, teaching methods, and techniques for them. This study was developmental research that aimed to describe the result of instructional media development of braille number card to improve blind students' understanding on integer number and describe their understanding after using braille number card as learning media at special needs elementary school. The subjects of this study consisted of three students with low vision, partially sighted students, and blind students. The research model used was ADDIE development model (analysis, design, development, implementation, and evaluation). Data were collected using test and questionnaire to know their understanding of braille number card as learning media on integer numbers. The result showed that blind students responded positively with an average score of 83% and 66.7% of their learning test. Therefore, It can be concluded that braille number card as instructional media can be used in teaching and learning activity to improve blind students' understanding.